The Singularity System. - LARUS, JAMES; HUNT, GALEN (Communications of the ACM, 2010)
The article presents information on the Singularity computer operating system being designed at the research branch of Microsoft Corp. It is noted that the majority of existing computer code is based on standards established prior to the 1980s, and that an operating system designed with 21st-century software engineering capabilities would be capable of significant performance improvement. Information on the techniques and principles used in the Singularity project is provided. The system is designed to be self-describing at every level of abstraction, in order to improve correctness. The ability of the system to contain software bugs is also discussed.